Effects of nutrient solution concentration on plant growth and phytochemical accumulation in substrate-grown spinach. - Machado, Rui M. A. (2021)
The effect of the electrical conductivity of a complete nutrient solution and of the spinach cultivar (Spinacia oleracea L. ‘Regia’ and ‘Manatee’) on the growth, nitrates, total phenols compounds, riboflavin, ascorbic acid, and photosynthetic pigments contents, antioxidant power (FRAP, DPPH) and ascorbate peroxidase activity was evaluated. Soil-blocked spinach seedlings (five seedlings per block) were transplanted (on 25 January 2018) at 18 days after emergence to Styrofoam planting boxes (100 cm long × 25 cm wide × 10cm high) filled with 14 L of substrate. Each planting box was irrigated daily by drip and fertilized with nutrient solution. The nutrient solution adopted had two concentrations of nutrients, corresponding to an EC of 1.2±0.2 and 1.7±0.2 dS m-1. Fresh yield was not to be found affected by the EC of the nutrient solution or by the cultivar. Shoot biomass percentage and leaf-blade NO3 increased as the EC of the nutrient solution increased. Leaf–blade riboflavin was found to be affected by the interaction between EC and cultivar, reaching the highest value in ‘Regia’ (565.06 μg 100 g-1 fresh weight) while EC 1.2 dS m-1. Nutrient solution EC was not found to have an influence on the content of total phenols compounds, ascorbic acid, chlorophyll a and b, carotenoids and ascorbate peroxidase. The cultivar was found to have an influence on nitrates and photosynthetic pigments content and ascorbate peroxidase activity.